Pengembangan Media Pembelajaran Fisika Berbantuan Scratch untuk Meningkatkan Kemampuan Problem Solving Peserta Didik - Novita Iriyanti Ningrum; Akhdinirwanto, Raden Wakhid; Fatmaryanti, Siska Desy; Kurniawan, Eko Setyadi (Jurnal Pendidikan Fisika dan Sains (JPFS), 2023)
This study aims to determine the feasibility in terms of validity, practicality, and effectiveness of Scratch assisted physics learning media to improve students problem solving abilities. This study uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of this study amounted to 12 students participating in the limited trial and 21 students participating in the wide trial. Based on the results of the study, it was obtained: (1) the results of the validation test of the Scratch assisted physics learning media were stated in the very good category assessed by two expert validators, (2) the developed media was declared practical as seen from the results of the implementation of the lesson plan which obtained a score of 95.1%, and (3) the media is said to be effective as seen from the results of the problem solving ability test which has increased in each indicator and the N-gain is 0.44 in the medium category. It was concluded that the Scratch assisted physics learning media in the study was declared valid, practical, and effective so that it was feasible to use it to improve students' problem solving abilities.